Polyethylene glycol (PEG) molecular weight influences the ClearT2 optical clearing method for spheroids imaging by confocal laser scanning microscopy - Costa, Elisabete Cristina da Rocha (2018)
Some fluorescence microscopies, like confocal laser scanning microscopy (CLSM), have limited penetration depth. Consequently, the visualization and imaging of 3D cell cultures, such as spheroids, can be a significant challenge. Therefore, to improve the imaging of 3D tissues, clearing methods have been optimized to render transparency to the opaque spheroids. In this work, the influence of the polyethylene glycol (PEG) molecular weight (MW) used in the ClearT2 method for the imaging of PI stained spheroids was investigated. The results demonstrated that ClearT2 clearing method contribution for spheroids transparency and preservation of the PI fluorescence intensity is independent on the PEG MW. However, the ClearT2 method performed using PEG 4000 Da allowed a better PI signal penetration depth and cross-section depth. Overall, the optimization of PEG MW can improve the imaging of intact spheroids by CLSM. Further, this work may also contribute to increase the application of 3D cell culture models by pharmaceutical industry in therapeutics high-throughput screening.